Urgensi Penerapan Insolvency Test Sebagai Bentuk Reformasi Hukum Kepailitan di Indonesia: Studi Perbandingan Dengan Amerika Serikat - Amina, Frahnaz (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Indonesia’s bankruptcy legal system remains formalistic, where Article 2 paragraph (1) of Law No. 37 of 2004 only requires two creditors and one due debt without examining the debtor’s financial capacity. This opens the door for abuse by bad-faith creditors and creates injustice for solvent debtors. This study examines the effectiveness of applying the insolvency test to prevent misuse of bankruptcy petitions and its urgency as a substantive requirement in Indonesia’s bankruptcy law reform. The method used is normative juridical research with statutory and comparative approaches. The study finds that the insolvency test, as adopted in the U.S. legal system under Chapter 11 of the U.S. Bankruptcy Code, ensures fair protection for both creditors and debtors. The conclusion emphasizes the necessity of explicitly regulating the insolvency test in Indonesia’s Bankruptcy Law. It is recommended that the Government, Supreme Court, and Financial Services Authority (OJK) take steps to harmonize regulations to enhance legal certainty, justice, and economic stability